Empowering Vocational Informatics Students with Android-Based Problem-Based Learning Media - Khakim, Muhamad Lutfi; Nidhom, Ahmad Mursyidun (Letters in Information Technology Education (LITE), 2024)
Technology is experiencing rapid development and is in line with the increasing need for adequate human resources (HR). There is a need for educators to prepare themselves to teach and produce high-quality individuals. However, many students are still not ready to enter the workforce. To prepare high-quality students, a good conceptual understanding is needed, and to achieve this, students must have strong learning motivation. One way to increase motivation is by using the Problem-Based Learning model and supported by Android-based learning media. The purpose of this research and development is to (1) Develop, (2) Test the feasibility, and (3) Determine the increase in student motivation in using Android-based learning media with a Problem-Based Learning model in Informatics subjects at vocational high schools that have been developed. The 4D model was chosen for this development, with stages including define, design, develop, and disseminate. The development result is an Android-based learning media called "Mepins" (Informatics Learning Media). The evaluation results obtained from material expert validation were 100 percent with very suitable criteria, the results from media expert validation were 81.09 percent with suitable criteria, the results from small-group development testing were 80.53 percent with suitable criteria, the results from large-group field testing were 86.32 percent with very suitable criteria, and the results from large-group motivation testing were 88.75 percent with very suitable criteria, with an N-Gain value of 0.54, which is interpreted as moderate. This indicates that implementing problem-based learning increases student motivation. Therefore, the media is considered suitable and can be used as a supporting learning media for Informatics subjects at vocational high schools